SWISSPAQ: validation of a new physical activity questionnaire in cardiac rehabilitation patients (Swiss Medical Weekly, 2013)
QUESTION UNDER STUDY: Physical activity is known to play an important role in protection against cardiovascular disease. At present, there is no validated questionnaire recording physical activity for German-speaking cardiac patients. The aim of this study was to develop and validate a new physical activity questionnaire for German-speaking patients attending a cardiac rehabilitation programme. METHODS: A questionnaire on physical activity was developed on the basis of personal and telephone interviews, using qualitative and quantitative approaches. The questionnaire was validated in 48 patients during or after cardiac rehabilitation. For this purpose, data on energy expenditure in MET (metabolic equivalent) hours per day, collected from the questionnaire, were compared with the results of combined heart rate and accelerometry measurement (ECG-accelerometry) using an ACTIHEART-monitor and a physical activity diary. Test-retest reliability was examined in a subset of 33 patients who completed the questionnaire twice within 3 weeks. RESULTS: There was a significant correlation between the questionnaire data and the ECG-accelerometry (r = 0.407, p = 0.004). The mean (± standard deviation) difference between the results derived from the questionnaire and those from ECG-accelerometry was 1.05 ± 4.79 MET-hours per day. The retest showed a correlation of r = 0.624 (p